The accounting standardization system in Portugal and its first-time adoption effects in the olive and cork tree cultures - Oliveira, J.; Azevedo, G.; Oliveira, M.; Almeida, S. (Academic Journal of Economic Studies, 2015)
This study examines the quantitative impact of the first-time adoption of the Portuguese Accounting Standardization System on individual annual reports of Portuguese unlisted companies in the cork and olive tree culture sector. Findings indicate that the items which showed significant changes in the transition from the previous accounting frame of reference to the Portuguese Accounting Standardization System are mainly those regarding to biological assets, inventories, liabilities, current ratio, and return on assets. The adoption of the Portuguese Accounting Standardization System has led generally to less conservative accounting practices, indicating that characteristics of code-law countries such as cultural aspects and country enforcement regimes did not influence the adoption of IAS/IFRS-based accounting standards by Portuguese unlisted companies in the cork and olive tree culture sectors.